2010
DOI: 10.1128/aem.02892-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Proteomic Analysis of Factors Affecting Serum Cholesterol Reduction by Lactobacillus acidophilus A4

Abstract: This article identifies novel factors involved in cholesterol reduction by probiotic bacteria, which were identified using genetic and proteomic approaches. Approximately 600 Lactobacillus acidophilus A4 mutants were created by random mutagenesis. The cholesterol-reducing ability of each mutant was determined and verified using two different methods: the o-phthalaldehyde assay and gas chromatographic analysis (GC). Among screened mutants, strain BA9 showed a dramatically diminished ability to reduce cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…In earlier studies conducted with lactic acid bacteria, an increase in the viability of the strains was observed, reaching 20 and 40% ratios in the presence of cholesterol. During assimilation, the bacterial population increased with regard to the time of incubation, indicating that cholesterol was not toxic to growing cells [Ahire et al, 2012;Lee et al, 2010].…”
Section: Coprecipitation Of Cholesterol With Deconjugated Bilementioning
confidence: 99%
“…In earlier studies conducted with lactic acid bacteria, an increase in the viability of the strains was observed, reaching 20 and 40% ratios in the presence of cholesterol. During assimilation, the bacterial population increased with regard to the time of incubation, indicating that cholesterol was not toxic to growing cells [Ahire et al, 2012;Lee et al, 2010].…”
Section: Coprecipitation Of Cholesterol With Deconjugated Bilementioning
confidence: 99%
“…Hypercholesterolemia in humans has been shown to play a major role in atherosclerosis, cardiovascular disease, including coronary heart disease and stroke as well as cerebrovascular diseases [2][3][4]. High cholesterol has also been associated with an increased risk of metabolic syndrome symptoms, including abdominal obesity (large waist circumference), hyperglycemia, hypertriacylglycerolemia and hypertension by as much as 3-fold [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al [35] demonstrated that short-chain fatty acid concentrations, specifically the molar proportion of propionate and/or bile salt deconjugation, comprised the major mechanism involved in the purported cholesterollowering properties of L. fermentum. Lee et al (2010) revealed that several regulatory proteins mediated serum cholesterol reduction by a probiotic strain [36]. Lactic acid bacteria, including L. fermentum strains, could assimilate cholesterol, and thus, lower serum cholesterol levels [37].…”
Section: Discussionmentioning
confidence: 99%